Performance of Routing Protocol in MANET with Combined Scalable Video Coding - Parma Hadi Rantelinggi; Fridolin Febrianto Paiki; Kalvein Rantelobo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Development of wireless network technology to support various types of information services continues to increase especially in video streaming services. Video transmission especially in Mobile Ad Hoc Network (MANET) environment used in this research, particularly in the Combined Scalable Video Coding (CSVC) scheme which is a development of H.264 / MPEG-4. The contribution of this research focuses on the analysis of the performance of AODV, DSDV and DSR routing protocols in the MANET environment for CSVC, which is a new scheme in the development of H.264 / MPEG-4  video schemes. Performance evaluation are measured using the NS-2 simulation that supports MANET environment. As test metrics in this study are the end-to- end delay and PSNR. The test result shows the end-to-end delay in AODV is 0.60 seconds; this is lower than results on DSDV and DSR. On PSNR, DSR simulation results show 16.2 dB. This result exceed those in AODV and DSDV. The results of this research evaluation are influenced by channels in wireless networks, the larger the wireless network channel the more streaming video frames can be accepted by the destination node.